THE ASSOCIATION OF MATERNAL HLA-DRB1* WITH RISK OF DEVELOPMENT CONGENITAL SEPTAL HEART DEFECTS AT THEIR CHILDREN - Андрей Владимирович Шабалдин; Анна Викторовна Цепокина; Надежда Алексеевна Литвинова; Светлана Александровна Шмулевич; Павел Михайлович Крюков (The Publishing House Medicine and Enlightenment, 2016)
HLA-DR locus includes immune response genes (Ir), which are controlled by thymus-dependent immune responses to endobiotiki and xenon. In pregnancy, maternal microenvironment Ir genes may determine the effectiveness of the protection of the embryo and fetus by teratogens. Accordingly, the purpose of the present study was to investigate the contribution of women of alleles and genotypes of the gene HLA-DRB1* in the risk of septal congenital heart diseases. The comparative analysis (case-control) allele frequencies and genotype HLA-DRB1* women who have children with septal congenital heart disease (experimental group, n = 97) and women with healthy children (control group, n = 54). HLA-DRB1*03 and HLA-DRB1*11 were associated with a high risk of developing CHD: HLA-DRB1*03 (OR = 5,56) and HLA-DRB1*11 (OR = 4,31). Showing and protective against this disease allele HLA-DRB1*12 (OR = 0,28) and genotype HLA-DRB1*01,12 (OR = 0,06).